ECOLOGICAL OPTIMIZATION OF INTERNAL COMBUSTION ENGINES (International journal of artificial intelligence, 2026)
Although electric vehicles are on the rise, internal combustion engines (ICEs) remain dominant in global transportation. This article explores ecological optimization methods, including fuel modification, exhaust gas recirculation, and hybrid system integration to reduce emissions and improve efficiency.